Does "100% renewable" trump concern for spatial impacts?. (July 2019) - Herendeen, Robert
Abstract: I live in Burlington (pop. 43, 600), state of Vermont (pop. 624, 000), USA (pop. 326, 000, 000). We are the first U.S. city to become 100% renewable in electricity. We get hydro electricity from as far away as 700 km. (in Quebec, Canada) and as close as 1 km. Our wind electricity comes from sources 25–250 km distant. Our 50 MWe biomass plant burns forestry residues harvested within 160 km. Burlington now plans to become a "net-zero energy" city by 1. providing this renewable electricity (more) locally, and 2. extending coverage to present uses of fuel oil, petrol, and natural gas, with the notable exception of airplane fuel. This spatial reach has historically been de-emphasized in waves of enthusiasm for energy efficiency, sustainability (often loosely defined), and now renewability-especially in confronting greenhouse gas (GHG) emissions. I briefly review this history, and then present quantitative spatial impacts of Burlington's plans. Highlights: Since ca. 1970 several concepts have sequentially dominated energy issues. The latest, renewability, tends to de-emphasize questions of spatial impact. Burlington, Vermont, plans to become a "net-zero energy" city. I present some evaluations of the spatial implications of this plan.